Business model design in sustainable entrepreneurship: Illuminating the commercial logic of hybrid businesses. (1st March 2018) - Hahn, Rüdiger; Spieth, Patrick; Ince, Inan
Abstract: Sustainability entrepreneurs often rely on innovative approaches and business models to build a commercial logic for achieving social or ecological goals. We employ a deductive multiple-case study that builds upon a business model design framework to illuminate the commercial logic of hybrid/sustainable businesses. We identify four clusters of design themes and elements: niche novelty, integrated novelty, intermediary approaches, and platform approaches. We link our findings to the extant literature and provide suggestions for researchers and sustainable entrepreneurs for putting these design elements and themes into practice.